Study on groundwater potential as alternative water supply in Kuantan and Bentong, Pahang - Mohd Salamuddin, Ab Salam @ Nawi (2010)
The knowledge of groundwater resource in Pahang is low compared to the other state because Pahang received a large amount of rainfall each year which are between 2032 mm to 2540 mm. Consequently, the demand for groundwater is very low. Despite this, development of groundwater needs to be done to supply water to the public demand and to avoid the lack of water in the dry season. Aware of this fact, two areas in Pahang which are Kuantan and Bentong were selected as study areas. The study involved analysis of data pumping test collected from Mineralogy and Geoscience Department Pahang. The type of aquifer of both places is unconfined aquifer. In this study, Mineralogy and Geoscience Department have provided sufficient data for the analysis of this aquifer. The data collected are constant rate pumping test data, recovery pumping test data and step pumping test data. The study has found that, both of study areas have different geology which Kuantan is sand and gravel while Bentong is rock. Hydraulic conductivity, K for Kuantan is in region 700m/day to 2500m/day and Bentong is in reion im/day to 3 rn/day. Tranmissivity, T of aquifer in Kuantan is in region 3000 in /day to 9000 m 2 /day and Bentong is in region 4 m 2 /day to 12m 2 /day. Besides that, the well efficiency, E in Kuantan shows a high efficiency than Bentong which the value is 89% and 47.42% respectively. Furthermore. Average iron content in groundwater in Kuantan is 5 ppm exceeding the maximum iron content as stated in Ministry of Health Malaysia Standards. However iron content in this well can be reduced by river infiltration through the well. While water quality in Bentong shows the value for each element is acceptable in Ministry Of Health Malaysia. From this study, the results indicated that Kuantan area has a potential for groundwater development in Pahang compared to Bentong area.